2013
DOI: 10.1089/jpm.2012.0370
|View full text |Cite
|
Sign up to set email alerts
|

Suffering Assessment: A Review of Available Instruments for Use in Palliative Care

Abstract: By taking into consideration all features of the assessment instruments under review, the evaluation of suffering can be made easier. A wide and ever expanding range of approaches is now available, which facilitates the selection of the suffering-assessment instrument that is best suited to the needs of the specific patient. One of the challenges ahead will be to further analyze the psychometric properties of some existing instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 74 publications
0
49
0
5
Order By: Relevance
“…34 In fact, in our previous studies most patients with endstage dementia had a high suffering level upon their demise. 35 The suffering assessment [36][37][38][39][40] and quality of dying evaluation [41][42][43] are important in advanced dementia. Some available instruments developed for suffering assessment are Initial assessment of suffering, 44 Pictorial Representation of Illness and Self Measure, 45 Suffering Assessment Tool, 46 State of Suffering-V, 47 The Suffering scales, 48 and Structured Interview for Symptoms and Concerns scale.…”
Section: Discussionmentioning
confidence: 99%
“…34 In fact, in our previous studies most patients with endstage dementia had a high suffering level upon their demise. 35 The suffering assessment [36][37][38][39][40] and quality of dying evaluation [41][42][43] are important in advanced dementia. Some available instruments developed for suffering assessment are Initial assessment of suffering, 44 Pictorial Representation of Illness and Self Measure, 45 Suffering Assessment Tool, 46 State of Suffering-V, 47 The Suffering scales, 48 and Structured Interview for Symptoms and Concerns scale.…”
Section: Discussionmentioning
confidence: 99%
“…Studies and systematic reviews have shown that the use of such standardized quality of life assessment instruments, including patient‐reported outcome measures (PROMs) and patient‐reported experience measures (PREMs), can enable professionals to efficiently assess and address fluctuations in patients' various concerns. Providing clinicians with quality of life information can improve clinician‐patient communication, raise awareness of problems that would otherwise be overlooked, improve care plans and enhance multidisciplinary collaboration (Antunes, Harding, & Higginson, ; Catania et al., ; Krikorian et al., ).…”
Section: Dialectics Between Individualization and Standardizationmentioning
confidence: 99%
“…In most palliative literature, the notion of person-centred care is implicit, with sparse explications of person-centred approaches to palliative care. Moreover, conceptualizations in the literature tend to portray the patient with suffering detached from capability and agency (e.g., Kamal, Gradison, Maguire, Taylor, & Abernethy, 2014;Krikorian, Limonero, & Corey, 2013).…”
Section: Positioning Person-centred Carementioning
confidence: 99%
“…According to a recent review [32], there are 10 instruments available for assessing suffering for both research and clinical purposes. Among all the examined instruments, Pictorial Representation of Illness and Self-Measure (PRISM) showed the best psychometric properties, such as construct validity and test-retest reliability, and exhibits ease of readability and comprehension, as well as sensitivity to change.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that PRISM does indeed measure suffering [33]. So far, it has been validated for use with a number of patient populations, including patients with systemic lupus, vitiligo, obesity, lung disease, psoriasis, chronic noncancer pain, diabetes, fertility problems, and breast cancer [32, 34]. To date however, PRISM has not been used for assessing suffering in IBS patients.…”
Section: Introductionmentioning
confidence: 99%